THE EFECT OF ENVIRONMENTAL TECHNIQUE TO THE STUDENTS ACHIEVEMENT IN LEARNING VOCABULARY IN JUNIOR HIGH SCHOOL AT BATAM - Warno Edi (CAHAYA PENDIDIKAN, 2017)
This study was aimed to identify English as an international language is used in countries throughout the World, including Indonesia. Last few years, English has been taught at Junior High School. It has been accepted in Indonesia in line with the government’s plan on the nine-year compulsory study. Based on the 2013 curriculum, English at Junior High School level is taught as local content to serve the need of the local community. Thus, this study attempted to use an action research as methodology in teaching English vocabulary to young learners, particularly to the first graders.  In applying this study, the writer use the instruments.The instruments of the study in this research are a Environmental technique, tests, field notes and a questionnaire.After giving all the instrument, the writer analyze the result using statistical formulas. Then the writer compared the results in pre-test and post-test. The students’ mastery of vocabularies of fruits, animals, road sign, parts of body, and things in the classroom have improved after the Environmental techniques was given. It was supported by the significant different result of the pretest that was lower (56.64%) than post-test (96.19%).